2005
DOI: 10.1093/toxsci/kfi256
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity of Nanoparticles in Mammalian Germline Stem Cells

Abstract: Gametogenesis is a complex biological process that is particularly sensitive to environmental insults such as chemicals. Many chemicals have a negative impact on the germline, either by directly affecting the germ cells, or indirectly through their action on the somatic nursing cells. Ultimately, these effects can inhibit fertility, and they may have negative consequences for the development of the offspring. Recently, nanomaterials such as nanotubes, nanowires, fullerene derivatives (buckyballs), and quantum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
620
2
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,106 publications
(675 citation statements)
references
References 48 publications
30
620
2
6
Order By: Relevance
“…Previous studies demonstrate that NPs have the capacity to penetrate the blood-testis barrier and some of them have toxic action on male germ cells [30][31][32][33]. Braydich-Stolle et al showed that mammalian spermatogonial stem cells are sensitive to Ag-NPs [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrate that NPs have the capacity to penetrate the blood-testis barrier and some of them have toxic action on male germ cells [30][31][32][33]. Braydich-Stolle et al showed that mammalian spermatogonial stem cells are sensitive to Ag-NPs [5].…”
Section: Discussionmentioning
confidence: 99%
“…Many recent in vivo and in vitro studies demonstrate that most nanoparticles (NPs) show an adverse or toxic effect on male germ cells [4,5]. NPs are materials with at least one dimension ≤100 nm, and this large surface-to-volume ratio results in unique characteristics compared to their corresponding bulk materials [6].…”
Section: Introductionmentioning
confidence: 99%
“…Braydich-Stolle et al showed that mammalian spermatogonial stem cells are sensitive to TNP [5]. Gromadzka-Ostrowska et al demonstrated that even small amounts of silver NPs had a toxic impact on the germ cells and reduced sperm quality [31].…”
Section: Discussionmentioning
confidence: 99%
“…Many recent in vivo and in vitro studies demonstrate that most nanoparticles (NPs) have an adverse or toxic action on male germ cells [4,5]. NPs are materials with at least one dimension ≤100 nm, and this large surface-to-volume ratio results in unique characteristics compared to their corresponding bulk materials [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that kinematic parameters of sperm was progressively reduced by higher concentrations of nanosilver in vitro (Mirshokraei et al, 2011). Following exposure to silver nanoparticles, liver, neuroendocrine and germ cell lines have shown impaired function of mitochondria (Braydich-Stolle et al, 2005;Hussain et al, 2005;Hussain et al, 2006). This characteristic of response was similar in all cells.…”
Section: Discussionmentioning
confidence: 76%